2016
DOI: 10.1002/adma.201604113
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Perovskite Thin‐Film Photovoltaics: In Situ Diagnostics and Importance of the Precursor Solvate Phases

Abstract: Solution-processed hybrid perovskite semiconductors attract a great deal of attention, but little is known about their formation process. The one-step spin-coating process of perovskites is investigated in situ, revealing that thin-film formation is mediated by solid-state precursor solvates and their nature. The stability of these intermediate phases directly impacts the quality and reproducibility of thermally converted perovskite films and their photovoltaic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
209
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 173 publications
(224 citation statements)
references
References 56 publications
10
209
2
1
Order By: Relevance
“…In recent years, in situ time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) has emerged as an effective method to monitor solid‐state thin film formation and microstructure evolution during solution casting of ink‐based semiconductors . More recently, it has also been used successfully to investigate crystallization behavior for 3D and reduced dimensional perovskites solution‐cast using spin‐coating and blade‐coating . Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, in situ time‐resolved grazing incidence wide‐angle X‐ray scattering (GIWAXS) has emerged as an effective method to monitor solid‐state thin film formation and microstructure evolution during solution casting of ink‐based semiconductors . More recently, it has also been used successfully to investigate crystallization behavior for 3D and reduced dimensional perovskites solution‐cast using spin‐coating and blade‐coating . Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance .…”
Section: Introductionmentioning
confidence: 99%
“…Chen and coworkers found the coexistence of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in the intermediate phase of MAPbI 3 perovskite and accordingly fine‐tuned the quality of films by adjusting DMSO concentration to further improve solar cell performance . We previously reported that solution‐processed MAPbI 3 and PbI 2 have a propensity to form intermediate‐ordered precursor phases, which can fully solidify into solvate co‐crystals during solution processing, as revealed by in situ diagnostics . In contrast, the addition of significant amounts of Br and Cl significantly inhibited solvate co‐crystallization, pointing to the importance of halide‐mediation in Pb‐solvent complexation .…”
Section: Introductionmentioning
confidence: 99%
“…Several groups studied the role of lead precursors, like PbI 2 , PbCl 2 and PbAc 2 . [19,[27][28][29] www.advancedsciencenews.com presence of chloride, either through methylammonium chloride (MACl) or PbCl 2 , the crystallization kinetics seem to change dramatically. This is further discussed in Section 2.3.…”
Section: One-step (Solvent Engineering)mentioning
confidence: 99%
“…[18,[22][23][24] The interactions between perov skite films and various volatile solvents have been investigated, where the effects on film compositions and morphologies are observed. [27][28][29][30][31][32][33] The degradation of perovskite materials under high temperatures and water vapor atmospheres has also been investigated to tackle the stability issue. [22][23][24] These impacts on perovskite films could profoundly affect the performance of the final devices.…”
mentioning
confidence: 99%